Plant defense elicitors: plant fitness versus wheat stem sawfly - Govinda Shrestha; Shabeg S. Briar; Gadi V.P. Reddy (PeerJ, 2018)
The wheat stem sawfly (WSS), Cephus cinctus Norton, is an important wheat pest in the Northern Great Plains of the USA. No single control measure effectively suppresses WSS damage. This study provides information on the effects on the WSS adult settling preference behavior on wheat plants under laboratory conditions from treatment with both synthetic plant defense elicitors (Actigard® and cis-jasmone) and a botanical insecticide (Azadirachtin®). In addition, field experiments were performed to determine whether these chemicals impact the WSS fitness (larval mortality and larval body weight), winter wheat plant fitness (infestation, stem lodging, yield, and quality), adult population of WSS and Bracon spp., and larval parasitism levels. Our lab results showed that there were no significant differences in adult settling behavior on plants exposed separately to each chemical and control. In contrast, when adults were exposed simultaneously to treated and untreated plants, there was a significant reduction in the percentage of adults settling on Actigard® and Azadirachtin® treated plants compared to plants sprayed with water in the same cage. However, in field situations, regardless of application timing and field location, none of the chemicals significantly reduced adult population or stems damage. The exception was two times applications of Actigard® had significantly lower WSS infested stem damage levels at 30 days after initial treatment applications at Knees and 50 days at Choteau locations compared to control, but without effect at the Conrad location. The field study indicated that two times applications of Actigard® significantly increased diapausing larval mortality percentages and lowered stem lodging levels compared to untreated controls at Knees and Choteau locations, while no effects at Conrad location. Larval body weight was significantly lower in plots treated with Actigard® at Knees and Conrad, but no effects at Choteau. No significant differences were found in wheat yield and quality in plots treated with chemicals and controls at any location. Bracon spp. adult population and parasitism levels were not negatively affected by the use of chemicals. In conclusion, this study offers insights on what treatments should be emphasized in more detail despite variable findings.